Fermented Camel (Camelus dromedarius) and Bovine Milk Attenuate Azoxymethane-induced Colonic Aberrant Crypt Foci in Fischer 344 Rats - Amr, Amira M.; Takruri, Hamed R.; Shomaf, Maha S.; Alhaj, Omar A.; E. Faris, Mo'ez Al-Islam; Abdel-Rahman, Wael M. (Pakistan Journal of Nutrition, 2018)
Background and Objective: Camel milk is a folk remedy that includes valuable nutrients and bioactive zoochemicals. However, the chemopreventive potential of camel milk against colon carcinogenesis is poorly understood. This study was conducted to investigate the chemopreventive potential of camel (Camelus dromedarius) and bovine milk as well as the impact of fermenting these milks with Lactobacillus acidophilus and Streptococcus thermophilus against early colon carcinogenesis as measured by the reduction of aberrant crypt foci (ACF) in azoxymethane (AOM)-treated Fischer 344 rats. Methodology: Each of 60 weanling male rats was assigned to one of 6 experimental diet groups: Fermented and unfermented camel milk with AOM, fermented and unfermented bovine milk with AOM and positive (PC, AOM only) and negative (NC, saline vehicle only) control groups. The animals were fed the corresponding diets for 3 weeks and then received two subcutaneous injections of AOM or vehicle for 2 consecutive weeks and they were then placed on the corresponding diets for 11 weeks. At termination, all rats were euthanized, colons were harvested and the ACF counts were determined for all tested groups. Immunohistochemical testing was then performed to examine cell proliferation and apoptosis in the camel milk groups. Results: Significant reductions (p<0.05) (48.4-62.1%) in the total ACF count were observed in the colons of the rats fed all milk diets compared with rats fed on PC. However, significant differences were not observed in the total ACF between the camel and bovine milk diets or between the fermented and unfermented milk diets. In addition, significant changes were not observed in the apoptotic index for the camel milk diet compared with the index values for PC and β-catenin was generally localized to the membrane in all examined specimens. Conclusion: By virtue of its bioactive components, camel milk exhibited a chemopreventive potential against early colon carcinogenesis, however, fermentation did not improve its chemopreventive potential.